The Effect of Health Promotion (With MCH Book) on Knowlegde, Attitude, Behavior of Utilizing MCH Books in Pregnant Women at UPTD Public Health Center of Pati Distric - Retnoningsih, Heriani; Yuniastuti, Ari; Zainafree, Intan (Public Health Perspective Journal, 2024)
Health level is a measure of a country’ welfare. The purpose of this study was to determine the  impact  of health promotion with maternal and child health (MCH) books on knowledge, attitudes and health behavior of pregnant women at the UPTD Health Center of Pati Regency because high maternal mortality rate (MMR) indicates that maternal health is still poor.  The type of research is Quasy-Experiment (pre-experimental designs). The research design used Pretest-Posttest Control Group design. Sampling in this study was non-random sampling with purposive sampling type. Based on the population of pregnant women in 29 UPTD Health Centers in Pati regency, 2 Health Centers were determined to be objects of research, namely UPTD Kayen Health Center and UPTD Pati II Health Center. The results showed that frequency distribution of respondents’ answers in the control group or Pati II Health Center showed that the pretest and posttest values in responents did not increase in the value of the knowledge variable of pregnant women. Meanwhile, the frequency distribution of the respondents showed the pretest and posttest  in the experimental group or Kayen health Center respondents, where there was an increase in the value of the variable of knowledge of pregnant women which was getting better. The results of the Wilcolzon Signed Rank  Test in the control group showed that the sig pretest and posttest values of the behavioral variables in the control group were > 0.05 so it can be concluded that there was no change in the behavior or pregnant women in the control group. The results of the Wilcoxon signed rank test in the intervention group showed that the sig pretest and posttest values of the behavioral variables of pregnant women in the experimental group were <0,05 so it can be concluded that there was a change in the behavior of pregnant women in the intervention group.